2017
DOI: 10.1155/2017/6327180
|View full text |Cite
|
Sign up to set email alerts
|

The Global Lung Function Initiative 2012 Equations Are as Well-Suited as Local Population Derived Equations to a Sample of Healthy Professional Firefighters

Abstract: Background and Objective We aimed to assess the validity of using the Global Lung Function Initiative's (GLI) 2012 equations to interpret lung function data in a healthy workforce of South Australian Metropolitan Fire Service (SAMFS) personnel. Methods Spirometry data from 212 healthy, nonsmoking SAMFS firefighters were collected and predicted normal values were calculated using both the GLI and local population derived (Gore) equations for forced expiratory volume in one second (FEV1), forced vital capacity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Several studies based their conclusions on the published predicted values of spirometric indices (FEV 1 and FVC), which have been reviewed or modified over the years. The Global Lung Function Initiative developed in 2012 (GLI-2012) reports the latest reference equations for spirometry, based on the pooled resources of various countries and on data obtained from more than 74,000 healthy non-smokers tests from all over the world [ 62 , 63 ]. To date, the GLI database is the one in force and is used by most of the researchers and health care professionals, hampering an appropriate comparison between studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies based their conclusions on the published predicted values of spirometric indices (FEV 1 and FVC), which have been reviewed or modified over the years. The Global Lung Function Initiative developed in 2012 (GLI-2012) reports the latest reference equations for spirometry, based on the pooled resources of various countries and on data obtained from more than 74,000 healthy non-smokers tests from all over the world [ 62 , 63 ]. To date, the GLI database is the one in force and is used by most of the researchers and health care professionals, hampering an appropriate comparison between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that in Australia the selection process to become a firefighter demands undergoing physical and psychological health and fitness tests and, once accepted, the selected individuals have to perform regular and intensive medical examinations. In addition, if they are not sufficiently healthy and fit, they are excluded and cannot proceed in their firefighter career [ 60 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Previous studies showed that the applicability of GLI-2012 was different in different countries or populations. [9][10][11][12][13][14] However, the values of GLI-2012 in North Chinese have not been fully investigated yet.…”
Section: Introductionmentioning
confidence: 99%